The Fractured-Land Hypothesis - Fernández-Villaverde, Jesús; Koyama, Mark; Lin, Youhong; Sng, Tuan-Hwee (Quarterly Journal of Economics, 2023)
Abstract Patterns of state formation have crucial implications for comparative economic development. Diamond (1997) famously argued that “fractured land” was responsible for China’s tendency toward political unification and Europe’s protracted polycentrism. We build a dynamic model with granular geographical information in terms of topographical features and the location of productive agricultural land to quantitatively gauge the effects of fractured land on state formation in Eurasia. We find that topography alone is sufficient but not necessary to explain polycentrism in Europe and unification in China. Differences in land productivity, in particular the existence of a core region of high land productivity in northern China, deliver the same result. We discuss how our results map into observed historical outcomes, assess how robust our findings are, and analyze the differences between theory and data in Africa and the Americas.